Pemikiran Tentang Pengembangan Pendidikan Islam Multikultural - Ach. Syaikhu (STAIFAS-Press, 2016)
Violence is always present everywhere. Oddly enough, religion is often used as a legitimacy in doing violent practices continued to be a prolonged conflict, Whereas religion is supposed to be the savior of the conflict to peace. Lately more and more prevalent in the country appears fundamentalism, radicalism, to terrorism, which would damage the unity of the nation. So that this issue does not continue to grow if it can be resolved need support from all walks of life with a mutual understanding on the differences. Thus, multicultural education must be signed in pen-education system so that learners have a sensitivity in the face of social phenomena that result from differences in ethnicity, race, religion, hoping tolerance will be upheld.Key Word: Thought, Islamic Education Development, Mulikultural.